[P021] Analysis and optimization of an interventional radiology procedure using a radiation dose index monitoring software. (August 2018) - Colombo, Paola Enrica; Rottoli, Federica; Sutto, Marina; De Mattia, Cristina; Rampoldi, Antonio; Torresin, Alberto
Abstract : Purpose: To use NEXO[DOSE]; a Radiation Dose Index Monitoring system, to collect and analyse dosimetric data to drive the optimization of interventional radiology procedure for prostatic artery embolization (PAE). Methods: NEXO[DOSE] extracts geometric (primary and secondary angles, table height) and dosimetric (irradiation type, KAP, voltage, filter) parameters from the Radiation Dose Structured Report, and calculates a skin dose map. This software separately lists the dose contribution from the acquisition mode and the fluoroscopy: this can help to quantify the contribution of the two acquisition types. We identify in our institution the PAE angiographic procedure as a high dose procedure, with high Kerma Area Product (KAP) compared to other interventional protocols. It was associated with high risk of skin lesions. A low dose protocol was introduced and phantom characterization, i.e. entrance dose and image quality (LCD), was assessed on various thickness of PMMA. It was necessary to use 30 cm of PMMA to better represent the patient geometry, considering that, in this procedure, the highest dose contributions came from events with oblique angles. After optimization, patient dose was monitored using KAP and peak skin dose. Results: We retrospectively analysed the exposure values of 84 patients, using NEXO[DOSE]. The acquisition dose in PAE is 70% of the total procedure: the first step was the introduction of an acquisition protocol with low entrance detector dose. The frame rate was reduced from 3 to 2 fps and additional X-ray filtration of 1 mm Al + 0.1 mm Cu was added. The fluoroscopy frame rate was also reduced from 15 to 7.5 fps. In the phantom the entrance dose was reduced by 49% and the LCD reduction was 30% for details dimensions from 0.5 to 6 mm. The physicians assessed the loss of image quality to be acceptable. The clinical procedures had a 60% KAP reduction and a 49% PSD reduction. Conclusion: The optimization process of PAE procedure led to a significant reduction of patient dose and a degradation of image quality that was judged satisfactory from physicians. This was the result of a multidisciplinary team work (physicians, technicians and medical physicists).